2020
DOI: 10.1021/acs.inorgchem.9b03274
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Properties of a Discrete Water-Soluble Prussian Blue Analogue FeII/CoIIICube: Confinement of a Water Molecule in Aqueous Solution

Abstract: A novel type of water-soluble anionic cubic cages K 4 [{Co III (Me 3-Tacn)} 4 {Fe II (CN) 6 } 4 ] and Na 4 [{Co III (Me 3-Tacn)} 4 {Fe II (CN) 6 } 4 ] were prepared by means of a mechanistically designed selfassembly process between [Co(Me 3-Tacn)Cl 3 ] and M 4 [Fe II (CN) 6 ] for M = Na or K, respectively; consisting on a rate limiting outer-sphere redox step followed by a fast substitution/inner-sphere redox reaction sequence. These compounds show a remarkable stability in aqueous solution at different pH ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 39 publications
(84 reference statements)
2
33
0
Order By: Relevance
“…56 The signal at 3.87 ppm is associated with water bound to residual amounts of Na + in the building block samples, which led to formation of the already described sodium salt of the cubic structure. 45 As for the signal at 4.21 ppm, it shows a very distinct line shape that is associated with coupling to a I = 3 / 2 spin nucleus in a very symmetrical environment, as expected for a small 7 Li center ( J H–Li = 1.1 Hz). Furthermore, the chemical shift (4.21 ppm), compared with that of encapsulated {Na–OH 2 } + (3.87 ppm), is consistent with a more acidic water molecule, as expected from the higher polarizing power of the attached lithium cation.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…56 The signal at 3.87 ppm is associated with water bound to residual amounts of Na + in the building block samples, which led to formation of the already described sodium salt of the cubic structure. 45 As for the signal at 4.21 ppm, it shows a very distinct line shape that is associated with coupling to a I = 3 / 2 spin nucleus in a very symmetrical environment, as expected for a small 7 Li center ( J H–Li = 1.1 Hz). Furthermore, the chemical shift (4.21 ppm), compared with that of encapsulated {Na–OH 2 } + (3.87 ppm), is consistent with a more acidic water molecule, as expected from the higher polarizing power of the attached lithium cation.…”
Section: Resultssupporting
confidence: 64%
“… 35 38 A concerted redox-triggered ligand substitution approach has led to the family of complexes indicated in Chart 1 , where cyanido ligands bridge the metal centers and the remaining coordination sites are occupied by a macrocyclic tri-, tetra-, or pentaamine (N 3 , N 4 , or N 5 ). 39 45 These cobalt/iron PBAs behave as discrete molecular Class II mixed-valence complexes with remarkable thermal and pH stability, as well as reversible redox reactivity; 44 , 46 49 this chemistry has successfully included other metals as well. 40 , 50 − 52 Potential applications of the redox properties of these complexes on inert supports have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Subsequently, a wide variety of multinuclear molecular PBAs with CTIST character was synthesized. [18][19][20][21][22][23][24][25][26][27][28][29] Apart from larger PBA units and network systems, 30 the field also evolved towards the smallest unit cell, the dinuclear [FeCo] PBA. 31,32 The first dinuclear PBA presented by Bernhardt et al, [33][34][35] however, showed neither thermal-nor photo-induced CTIST.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Subsequently, a wide variety of multinuclear molecular PBAs with CTIST character was synthesized. [18][19][20][21][22][23][24][25][26][27][28][29] Apart from larger PBA units and network systems, 30 the field also evolved towards the smallest unit cell, the dinuclear [FeCo] PBA. 31,32 The first dinuclear PBA presented by Bernhardt et al, [33][34][35] however, showed neither thermal-nor photo-induced CTIST.…”
Section: Introductionmentioning
confidence: 99%